Analisis Persaingan Pasar Tradisional dan Pasar Modern dalam Prespektif Daya Minat Beli Pengunjung - Christin Eva. S; Ivan Rivaldo Sihombing; Suandro Manik; Erika Erika; Tumiar Sidauruk (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
The development of the trade industry, the competition between the Traditional Market and the Modern Market has become increasingly significant in competing for the buying power of visitors. This study aims to find out the competition that occurs between modern markets and traditional markets based on the perspective of visitors' purchasing power. This research uses a descriptive approach which is an effort to understand social phenomena that occur through in-depth interpretation and analysis. Data collection was carried out through observation and direct interviews. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of the analysis show that the differences in characteristics between the two markets are that traditional markets offer unique cultural characteristics and traditional shopping experiences, while Modern Markets offer convenience, a wide variety of products, and modern facilities. Visitors' purchasing power is influenced by consumers' personal preferences, where traditional markets are more attractive to those who value interpersonal relationships and intimate shopping experiences, while modern markets are preferred by consumers who are looking for convenience and a diverse selection of products. The role of branding, marketing, and product innovation has a significant impact on the purchasing power of visitors in both types of markets. Traditional markets tend to rely on seller reputation and interpersonal relationships, while modern markets are more focused on digital marketing strategies and social media influencers